2014
DOI: 10.5751/ace-00628-090101
|View full text |Cite
|
Sign up to set email alerts
|

Variations in band reporting rate and implications for kill rate in Greater Snow Geese

Abstract: to 2005. We used a spatially explicit multinomial model based on 200 direct recoveries from 4256 banded geese to estimate reporting rate and harvest rate. We found that reporting rate for standard bands varied over time whereas harvest rate was higher in Canada than in the U.S. The reporting probability increased from 0.40 ± 0.11 in the first year of the study to 0.82 ± 0.14 and 0.84 ± 0.13 the second and third years, respectively. Overall, these reporting rates are higher than two previous estimates for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Thus, we suggest that it is highly unlikely that retrieval rate is constant across the 3 hunting seasons, between age groups, or across breeding latitudes, and suggest that it might also vary with changes in hunting regulations (Schulz et al ). Band reporting rate is also relatively poorly known but may be similarly variable (Souchay et al ). We suspect that some of our estimates (e.g., unusually high winter kill rate for AHY birds from the South in 2003 and 2013) could have reflected variation in λ or c , and suggest that greater attention should be devoted to understanding variation in bird retrieval and reporting rates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that it is highly unlikely that retrieval rate is constant across the 3 hunting seasons, between age groups, or across breeding latitudes, and suggest that it might also vary with changes in hunting regulations (Schulz et al ). Band reporting rate is also relatively poorly known but may be similarly variable (Souchay et al ). We suspect that some of our estimates (e.g., unusually high winter kill rate for AHY birds from the South in 2003 and 2013) could have reflected variation in λ or c , and suggest that greater attention should be devoted to understanding variation in bird retrieval and reporting rates.…”
Section: Discussionmentioning
confidence: 99%
“…2). If publications included data that had been reported elsewhere (Alisauskas et al 2011 andSouchay et al 2014 included data previously reported in Zimmerman et al 2009), we used only 1 source in our summary. Many recent studies have focused on adult male mallards because they have higher recovery probabilities than females and therefore provide more recovery data per deployed band (Royle and Garrettson 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Dead recoveries are widely interpreted as being proportional to the fraction of marked individuals that die from a given mortality factor in a given location during a given time interval, but additional variability can accrue from variation in the probability that a dead banded bird that is encountered is subsequently reported (Piper ). Incomplete reporting of banded birds found dead in the wild or harvested by hunters leads to reduced sample sizes, and hence less precise parameter estimates (Wilson et al ), but it can also lead to biased inferences, especially if reporting probabilities are non‐random with respect to other variables of interest (Souchay et al , Naef‐Daenzer et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the success of these combined measures in minimizing harvest of marked animals is not well‐documented. Although there is an abundance of literature that has demonstrated the effectiveness of incentive programs designed to increase hunter participation in research involving game species, such programs normally seek to increase the likelihood that hunters will take some desired action such as reporting harvests or completing harvest records (Bellrose , Kilpatrick et al , Royle and Garrettson , Zimmerman et al , Souchay et al ). Unfortunately, the same sort of incentive approach cannot be adopted by researchers to promote the voluntary restraint of actions such as harvesting marked research animals.…”
mentioning
confidence: 99%